2004
DOI: 10.1111/j.1365-2524.2004.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with variations in older people's use of community-based continence services

Abstract: Many people who have urinary incontinence and who may benefit from healthcare and professional advice do not currently access UK National Health Service services, even though effective treatments are available in the community. Older people have an increased prevalence of incontinence and a correspondingly increased need for continence services. Therefore, increasing older people's access to continence services has the potential to reduce inequalities and improve quality of life. The present study aimed to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 19 publications
0
30
1
Order By: Relevance
“…4 Chi-squared test for categorical variables and t-test for continuous variable to analyse sex differences in patients who sought help and in patients who did not seek help. 5 Á/not significant; *p B/0.05. [ ] the odds ratio is the difference between the group in brackets and the others.…”
Section: Resultsmentioning
confidence: 99%
“…4 Chi-squared test for categorical variables and t-test for continuous variable to analyse sex differences in patients who sought help and in patients who did not seek help. 5 Á/not significant; *p B/0.05. [ ] the odds ratio is the difference between the group in brackets and the others.…”
Section: Resultsmentioning
confidence: 99%
“…Data from Japan have con¢rmed that the psychometric properties of the questionnaire have been retained throughout this process [Subcommittee of Symptom and Quality of Life Assessment, 2001]. The ICIQ is being increasingly used and further evaluated in both clinical practice and research in the UK and internationally [Subcommittee of Symptom and Quality of Life Assessment, 2001; Karantanis et al, 2002;Peters et al, 2004]. Further research is required, however, to investigate its usefulness in routine clinical practice, for speci¢c groups, such as the frail elderly, and in the developing world.…”
Section: Discussionmentioning
confidence: 99%
“…Parametric and nonparametric analysis was conducted as appropriate. Binary logistic regression was used to assess the association between potential predictor variables and GHQ-12 and SCL-D caseness following methods recommended by Peduzzi et al 25 and Peters et al 26 Data reported are based on numbers of valid responses to items for each group or subgroup. Thus numerators and denominators may not always total to full sample size.…”
Section: Discussionmentioning
confidence: 99%